THE INFLUENCE OF SERVICE QUALITY, PERCEIVED VALUE, AND CUSTOMER SATISFACTION ON THE LOYALTY OF KRL COMMUTERLINE SOLO-JOGJA USERS - Taryza Carolina; Bambang Mursito; Sarsono Sarsono (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2023)
The purpose of this study was to determine the effect of customer satisfaction on KRL Commuterline Solo-Jogja user loyalty. The research was conducted on Solo-Jogja Commuterline KRL users. This research method is descriptive quantitative. The population is Solo-Jogja Commuterline KRL users in October-December 2022. A sample of 100 respondents uses a non-probability sampling technique where data is collected by questionnaire. Methods of data analysis with statistical analysis ie. multiple linear regression test, Fttest, t test and coefficient of determination. Data analysis was assisted with the helpiof SPSS software version 25. Based on the resultsifrom the study it can be seen that service quality has a positive and significant effect on KRL Commuterline Solo-Jogja user loyalty. As well as perceived value and customer satisfaction. Keywords: Customer Satisfaction, Perceived Value, Service Quality